Pool‐less processing to streamline downstream purification of monoclonal antibodies. Issue 2 (14th September 2016) - Zhang, Jennifer; Conley, Lynn; Pieracci, John; Ghose, Sanchayita
Abstract : With cell culture titers and productivity increasing in the last few years, pressure has been placed on downstream purification to look at alternative strategies to meet the demand of biotech products with high dose requirements. Even when the upstream process is not continuous (perfusion based), adopting a more productive and/or continuous downstream process can be of significant advantage. Due to the recent trend in exploring continuous processing options for biomolecules, several enabling technologies have been assessed at Biogen. In this paper, we evaluate the capability of one of these technologies to streamline and improve our downstream mAb purification platform. Current conventional downstream polishing steps at Biogen are operated in flow‐through mode to achieve higher loadings while maintaining good selectivity. As titers increase, this would result in larger columns and larger intermediate product pool holding tanks. A semicontinuous downstream process linking the second and third chromatography steps in tandem can reduce/eliminate intermediate holding tanks, reduce overall processing time, and combine unit operations to reduce validation burdens. A pool‐less processing technology utilizing inline adjustment functionality was evaluated to address facility fit challenges for three high titer mAbs. Two different configurations of polishing steps were examined: (i) anion exchange and hydrophobic interaction and (ii) anion exchange and mixed mode chromatography. Initial laboratory scale proof of concept studies showed comparable performance between the batch purification process and the pool‐less process configuration.